FBXW7 Reduces the Cancer Stem Cell-Like Properties of Hepatocellular Carcinoma by Regulating the Ubiquitination and Degradation of ACTL6A - Xing Wang; Ying Li; Yongning Li; Peng Liu; Songbai Liu; Yaozhen Pan (Stem Cells International)
Cancer stem cells (CSCs) comprise a subset of tumor cells that can initiate tumorigenesis and promote tumor advance. A previous study showed that the expression of FBXW7 in hepatocellular carcinoma (HCC) clinical samples was lower than that in the adjacent nontumor tissues and was negatively correlated with the invasion and migration of HCC cells. However, the biological characteristics and the underlying molecular mechanisms of FBXW7 in HCC stemness are yet to be elucidated. In present study, we found that FBXW7 participates in the self-renewal, tumorigenicity, sorafenib therapy, and stem cell-like properties of HCC cells in vivo and in vitro. The upregulation of FBXW7 inhibited the stemness and reduced the tumorigenicity and drug resistance of HCC cells. Mechanistically, proteins binding to FBXW7 were identified by coimmunoprecipitation and protein colocalization assays. We confirmed ACTL6A as a novel downstream target for FBXW7. The in vivo ubiquitination assay showed that FBXW7 repressed HCC malignancy by regulating the oncogenic activity of ACTL6A in a ubiquitin-dependent manner. Furthermore, we found that ACTL6A overexpression inversed the self-renewal abilities and tumorigenic abilities depressed by overexpressing FBXW7. The current findings suggested that FBXW7 reduces the stemness of HCC cells by targeting and degrading ACTL6A and provides a novel target for the diagnosis and treatment of HCC.